PEMANFAATAN PUPUK BOKASIH TERHADAP PENINGKATAN KESUBURAN FISIK DAN KIMIA TANAH PADA LAHAN PEMBUDIDAYAAN TANAMAN TOMAT (Lycopersicum esculentum MILL.) - Paulus O Lana; Charly Mutiara (AGRICA, 2017)
This study aims to determine the effect of bokashi fertilizer dosage on the physical and chemical properties of soil on tomato plants and the optimum dose of bokashi fertilizer which can provide the best influence on the physical and chemical properties of the soil. The research design used was a randomized block design (RBD) with a single factor pattern consisting of five treatments namely B0 = 0 tons ha-1 bokashi fertilizer (control), B1 = 5 tons ha-1 bokashi fertilizer, B2 = 10 tons ha-1 bokashi fertilizer, B3 = 15 tons ha-1 bokashi fertilizer, B4 = 20 tons ha-1 bokashi fertilizer. The observation variables in this study were soil volume/bulk density (gr /cm3), total soil pore space (%), N- total soil, available P-soil, available K-soil, soil C-organic, and soil pH. The results showed that the administration of bokashi fertilizer was able to improve the physical properties of soil in tomato plants, namely the weight of the soil volume decreased by 1,120 gr / cm³, water holding capacity increased by 30.24%, and soil pore space increased by 57.74%, so that the soil aggregate became good Giving doses of bokashi fertilizer can improve soil chemical properties in tomato plants, namely C-organic 0.91% very low, N-total soil 0.32% medium, P-available 37.25 ppm very high, and K-available 425.64 ppm very high and soil pH to 6.81 neutral. The supply of 20 tons/ha of bokashi fertilizer can improve soil physical and chemical properties optimally in tomato plants.